2015
DOI: 10.5455/msm.2015.27.347-350
|View full text |Cite
|
Sign up to set email alerts
|

Process Documentation: a Model for Knowledge Management in Organizations

Abstract: Background:Continuous and interconnected processes are a chain of activities that turn the inputs of an organization to its outputs and help achieve partial and overall goals of the organization. These activates are carried out by two types of knowledge in the organization called explicit and implicit knowledge. Among these, implicit knowledge is the knowledge that controls a major part of the activities of an organization, controls these activities internally and will not be transferred to the process owners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…The current review showed that some studies mentioned the acquisition and registration stages ( 30 , 34 ), while others only noted the registration ( 16 , 29 ) or the acquisition ( 13 , 33 , 35 ) in the documentation process.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The current review showed that some studies mentioned the acquisition and registration stages ( 30 , 34 ), while others only noted the registration ( 16 , 29 ) or the acquisition ( 13 , 33 , 35 ) in the documentation process.…”
Section: Resultsmentioning
confidence: 95%
“…The next step in experience documentation involves managers deciding and planning how to use and share the stored experiences by employees ( 13 , 16 , 29 , 30 , 32 - 35 ). The objective of knowledge application is to utilize documented knowledge by employees, enabling them to reference and employ the necessary knowledge before engaging in new programs and activities.…”
Section: Resultsmentioning
confidence: 99%